Pokémon. Sun & Moon. 3 - Kusaka, Hidenori; Turnage, Bryant (VIZ Media, LLC, 2019)
Sun and Moon hope to earn the right to compete and win the island challenge amulet, so they set out for Akala Island to be tested by the Trial Captains Kiawe, Mallow, and Lana. There, Sun has to first find then battle the powerful Totem Pokémon, while Moon goes hunting for a mysterious berry.